"You've Got to Rely on Yourself . . . and the State!": A Structural Chasm in the Chinese Political Moral Order - Xiang, B (Duke University Press, 2016)
China today is characterized by the coexistence of a relatively high level of stability at a national level and deep instabilities at the local level. On one hand, the ruling position of the Communist Party remains unchallenged in every formal way, and polls consistently report surprisingly high levels of public acceptance of the regime. On the other hand, social tensions run deep in everyday life, especially among laid-off workers, landless peasants, and badly exploited migrants. People’s frustration and anger are clear, but a sense of hope is also palpable. How should we make sense of this contradiction? And what does this mean for China’s political future?